Accuracy of Expressing Greetings, Farewells and Forms of Address in English by Taxy Drivers in Nusa Dua Resorts, Bali (LACULTOUR: Journal of Language and Cultural Tourism, 2024)
This study examines the accuracy with which taxi drivers at Nusa Dua International Resort in Bali express interrelated language functions, specifically greetings, farewells, and forms of address. Data were collected from 50 respondents through a test consisting of 14 situational questions in Bahasa Indonesia, yielding a total of 1,100 responses. The results indicate that 518 responses (47%) were correct, while 582 (53%) were incorrect. Among the 18 expected expressions, the three most common errors were found in "ladies and gentlemen" (92%), followed by "ladies and gentleman" (90%) and "sir (and) madam" (86%). Conversely, the three least common errors were in "good afternoon" (18%), "good morning" (16%), and "sir" (16%). These mistakes stem from a lack of familiarity with the expressions, often leading to a negative transfer from Bahasa Indonesia to English. Overall, respondents reported that greetings were the easiest language function while addressing proved to be the most challenging. The pedagogical implications of this study suggest that English language trainers should tailor their teaching to focus on expressions with higher error rates. The frequency and types of errors identified can serve as valuable discussion points in teaching sessions.